A direct requirement for Hedgehog signaling for normal specification of all ventral progenitor domains in the presumptive mammalian spinal cord - Wijgerde, Mark (Cold Spring Harbor Laboratory Press, 2002)
The hedgehog signaling pathway organizes the developing ventral neural tube by establishing distinct neural progenitor fates along the dorsoventral axis. Smoothened (Smo) is essential for all Hedgehog (Hh) signaling, and genetic inactivation of Smo cells autonomously blocks the ability of cells to transduce the Hh signal. Using a chimeric approach, we examined the behavior of Smo null mutant neural progenitor cells in the developing vertebrate spinal cord, and we show that direct Hh signaling is essential for the specification of all ventral progenitor populations. Further, Hh signaling extends into the dorsal half of the spinal cord including the intermediate Dbx expression domain. Surprisingly, in the absence of Sonic hedgehog (Shh), we observe the presence of a Smo-dependent Hh signaling activity operating in the ventral half of the spinal cord that most likely reflects Indian hedgehog (Ihh) signaling originating from the underlying gut endoderm. Comparative studies of Shh, Smo, and Gli3 single and compound mutants reveal that Hh signaling acts in part to specify neural cell identity by counteracting the repressive action of Gli3 on p0, p1, p2, and pMN formation. However, whereas these cell identities are restored in Gli3/Smo compound mutants, correct stratification of the rescued ventral cell types is lost. Thus, Hh signaling is essential for organizing ventral cell pattern, possibly through the control of differential cell affinities.